Analisis Model-model Blended Learning di Lembaga Pendidikan - sari, milya; asmendri, asmendri (Universitas Islam Negeri Imam Bonjol Padang, 2019)
The purpose of the study was to analyze the blended learning models used in various educational institutions. These blended models become references for educators who want to apply this model in their learning. The research method uses library research. The results of this research can be seen from many blended learning models used by various educational institutions. There are four MBL developed in US educational institutions, namely: rotation, flex, Self-blend and enriched-virtual models. There are also three possibilities for the development of MBL learning in education, namely web courses, web centric courses, and web enhanced courses. In addition, there are also five levels of ICT use in learning. Each model and type has advantages and disadvantages. Educators can combine or modify these models according to the conditions of their respective educational institutions..